2019
DOI: 10.7150/jca.33223
|View full text |Cite
|
Sign up to set email alerts
|

LOX inhibition downregulates MMP-2 and MMP-9 in gastric cancer tissues and cells

Abstract: Objective: The objective of this study was to analyze the effects of lysyl oxidase (LOX) on the expression and enzyme activity of the matrix metalloproteinases 2 (MMP-2) and 9 (MMP-9) and to study its preliminary effect mechanisms. Methods: We collected fresh cancer specimens from 49 gastric cancer patients who underwent surgery. Immunohistochemistry was used to quantitate the protein expression levels of LOX and MMP-9 in gastric cancer tissues and to analyze their correlation. Also, six-week old nude mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are zinc and calcium dependent proteases, which may degrade ECM components, promote angiogenesis and regulate cell adhesion. 31 Our Western blot and immunohistochemistry results showed that MCU knockdown significantly decreased the expression of MMP-2 protein in subcutaneous xenograft tumors induced by gastric cancer cells, confirming that MCU could be involved in the development of gastric cancer.…”
Section: Dovepresssupporting
confidence: 58%
“…Matrix metalloproteinases (MMPs) are zinc and calcium dependent proteases, which may degrade ECM components, promote angiogenesis and regulate cell adhesion. 31 Our Western blot and immunohistochemistry results showed that MCU knockdown significantly decreased the expression of MMP-2 protein in subcutaneous xenograft tumors induced by gastric cancer cells, confirming that MCU could be involved in the development of gastric cancer.…”
Section: Dovepresssupporting
confidence: 58%
“…For example, Yang et al (2013) [ 57 ] demonstrated that BAPN (500 µM) blocked the hypoxia-induced invasion and migration capabilities of cervical cancer cells. Zhao et al (2019) [ 58 ] have shown that the inhibition of LOX by BAPN in BGC-823 gastric cancer cells inhibits the expression and activity of matrix metalloproteinases 2 and 9.…”
Section: Lox Inhibitorsmentioning
confidence: 99%
“…Matrix metalloproteinase-2 is a determinant factor of cell migration. It enhances invasion of cancer cells via providing extracellular matrix (ECM) and basement membranes degradation [ 114 , 115 ]. Tissue inhibitors of metalloproteinases (TIMPs) are endogenous inhibitors of MMPs.…”
Section: Curcumin In Combination With Doxorubicinmentioning
confidence: 99%